Translation of the Risk Avoidance Partnership (RAP) for Implementation in Outpatient Drug Treatment Clinics. - Weeks, Margaret R; Kostick, Kristin; Li, Jianghong; Dunn, Jennifer; McLaughlin, Paul; Richmond, Phil; Choudhury, Shonali; Obidoa, Chinekwu; Mosher, Heather; Martinez, Maria (Journal of psychoactive drugs, 2015)
Scientific literature increasingly calls for studies to translate evidence-based interventions into real-world contexts balancing fidelity to the original design and fit to the new setting. The Risk Avoidance Partnership (RAP) is a health promotion intervention originally designed to train active drug users to become Peer Health Advocates. A theoretically driven approach was used to adapt RAP to fit implementation in outpatient methadone treatment clinics and pilot it with clinic patients. Ethnographic observations and process tracking documented the RAP translation and pilot experience, and clinic and community characteristics relevant to program implementation. Clinic administrators, staff, and patients were interviewed on their values, capacities, interest in RAP, perceived challenges of implementing RAP in drug treatment clinics, and experiences during the pilot. Findings indicated that RAP core components can be met when implemented in these settings and RAP can fit with the goals, interests, and other programs of the clinic. Balancing fidelity and fit requires recognition of the mutual impacts RAP and the clinic have on each other, which generate new interactions among staff and require ongoing specification of RAP to keep abreast of clinic and community changes. Collaboration of multiple stakeholders significantly benefited translation and pilot processes.